Combustion Characteristics of Municipal Solid Waste in a Grate-Fired Solid-Fuel Hot Water Boiler - Dias Raybekovich Umyshev; Andrey Anatoliyevich Kibarin; Aiganym Bulatkyzy Seidaliyeva; Dilshat Ozatuly Iskakov; Yeldos Lesbekovich Zhekenov; Ilyas Kermyly Jambayev; Madina Maratovna Umysheva (Energies)
Currently, ecological energy production is one of the most pressing issues in power engineering. In addition, environmental pollution caused by various emissions and the challenge of waste disposal remain significant global concerns. One potential solution to these problems is the conversion of waste into useful energy through combustion. In this study, experimental investigations were carried out on the combustion of municipal solid waste (MSW) in a grate furnace of a 400 kW hot water boiler. The experiments included the combustion of both MSW and traditional brown coal. Data were collected on the concentrations of various substances in the exhaust gases, and thermal imaging was performed to assess heat losses from the boiler surface. When burning waste compared to coal, SO2 concentrations were significantly lower, ranging from 3.43 to 4.3 ppm, whereas for coal they reached up to 122 ppm. NOX concentrations during MSW combustion peaked at 106 ppm, while for coal combustion they reached 67.5 ppm. A notable increase in CO concentration was observed during the initial phase of coal combustion, with levels reaching up to 2510 ppm. The thermal efficiency of the boiler plant reached 84.4% when burning waste and 87% when burning brown coal.